MANAJEMEN PERUBAHAN PENDIDIKAN ISLAM TRANSFORMATIF DALAM MENINGKATKAN MUTU PENDIDIKAN “STUDI KASUS DI MTsN 8 KEDIRI" - Susanto, Badik; Maunah, Binti; Safi’i, Asrop (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In the context of Islamic education, change management aims to change and improve the education system to be able to answer the challenges of the times and meet the needs of the community for quality education. MTsN 8 Kediri is one example of an Islamic education institution that implements transformative Islamic education change management. The research method used is a case study with a qualitative approach. Data were collected through interviews, observation and documentary research. The results showed that MTsN 8 Kediri has implemented transformative Islamic education change management through several steps, namely: 1) analyzing the need for change, 2) developing a vision, mission, and goals of change, 3) developing a change strategy plan, 4) implementing change, and 5) conducting evaluation and continuous improvement. The changes made have a positive impact on improving the quality of education at MTsN 8 Kediri, which can be seen from the increase in academic achievement, competency-based curriculum development, increased teacher competence, and improved infrastructure.